1988
DOI: 10.1016/0020-7292(88)90329-3
|View full text |Cite
|
Sign up to set email alerts
|

The problem of grandmultiparity in current obstetric practice

Abstract: A retrospective analysis of 646 Arab grandmultiparas who booked for hospital confinement between 1983 and 1985 was carried out. The results were compared with that of non-grandmultiparas during the same period. In the grandmultiparas, the incidences of gestational diabetes, hypertension rheumatic heart disease, antepartum, postpartum hemorrhage and macrosomic infants were increased. However, contrary to some previous reports the incidences of anemia, cesarean sections, induced labor, dysmaturity and perinatal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 3 publications
2
23
0
Order By: Relevance
“…While many antenatal and intrapartum complications like diabetes (overt and gestational), anemia, preterm delivery, malpresentation at term, postpartum hemorrhage, macrosomia showed a significant linear increase with increasing parity as indicated by v 2 test for linear trend (Fig. 1) as also reported by many other studies [3][4][5][6][7][8][9]; there were some, like the need for labor augmentation with its attendant risks specially in women of higher parity and soft tissue injuries, which showed a significantly declining trend with increasing parity as indicated by v 2 test for linear trend (Fig. 2).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…While many antenatal and intrapartum complications like diabetes (overt and gestational), anemia, preterm delivery, malpresentation at term, postpartum hemorrhage, macrosomia showed a significant linear increase with increasing parity as indicated by v 2 test for linear trend (Fig. 1) as also reported by many other studies [3][4][5][6][7][8][9]; there were some, like the need for labor augmentation with its attendant risks specially in women of higher parity and soft tissue injuries, which showed a significantly declining trend with increasing parity as indicated by v 2 test for linear trend (Fig. 2).…”
Section: Discussionsupporting
confidence: 77%
“…Most of the studies in the literature have compared the outcome between women of low parity (parity 2-4) and grand multiparty (parity [5][6][7][8][9], but only few studies have compared the outcome between the three groups as defined by International Federation of Gynecology and Obstetrics: lower parity (parity 2-4), grand multiparity (parity [5][6][7][8][9] and great grand multiparity (parity 10 and above).…”
Section: Introductionmentioning
confidence: 99%
“…Although the occurence of grandmultiparity in developed countries is declining, the desire for many children still exists within certain religious and cultural communities (Tanbo and Bungum 1987;Mwambingu et al 1988;Baskett 1977;Fuchs et al 1985). The risk of complications in pregnancy, delivery and post partum, among grand multipara has recently been evaluated by a number of investigators with conflicting results (Tanbo and Bungum 1987;Mwambingu et al 1988;Baskett 1977;Fuchs et al 1985;Opaneye 1986;Melesh 1986;Aziz 1980;Seidman et al 1988;Seidman et al 1987;Eidelman et al 1988;Chang et al 1977;A1-Sayeh and Hathout 1974). Some studies found the mothers at a significant risk for diseases of pregnancy and neonatal morbidity and mortality (Tanbo and Bungum 1987;Mwambingu et al 1988;Basket 1977;Fuchs et al 1985;Opaneye 1986;Melesh 1986;Aziz 1980).…”
Section: Introductionmentioning
confidence: 96%
“…4,[6][7][8][9] -Multiparity‖, from the introduction of the term had been regarded -dangerous‖ and an independent factor in maternal and infantile morbidity and mortality 7,[10][11][12][13][14] . Although some other works tried shifting the blame to other factors including: poor perinatal care 2,6,[15][16][17][18][19], interpopulation differences 20 , poor socio-economic status [23][24][25] as well as advanced maternal age [28][29][30][31] .There has been repeatedly mixed results as various researchers have observed inconsistent outcomes in seemingly similar populations.…”
Section: Introductionmentioning
confidence: 99%
“…In other words; high parity may not be a great cause for concern if the economy is stable, population is healthy and there is access to high quality medical care [23][24][25] . Thus, in a healthy population that has access to modern medical care, even refugee status did not count 26 .‖In every country, mothers and children constitute a major segment of the total population.…”
Section: Introductionmentioning
confidence: 99%